On the correlation between static and dynamic mechanical properties in architected lattice materials - Abdulla Alhembar; Imad Barsoum; Fabrizio Scarpa (Materials & Design, 2025)
Metamaterials are multiscale architected structures with design inspired by nature, which can offer multifunctional properties that surpass those of conventional materials. The static and dynamic mechanical properties of architected materials have been extensively investigated, however, their interrelationships are yet to be explored. This study correlates quasi-static and dynamic responses in 13 bio-inspired, topology-optimized, TPMS, plate- and truss-based lattices. Strong correlation between compressive modulus (Ec) and specific energy absorption (SEA) is found through experimental compression tests and low-velocity impact tests, supported by validated numerical modeling. For a subset of these lattices, the perforation limit (Vp) also exhibits a robust correlation between compressive modulus and SEA. Two in-house designs, the topology-optimized CompIED and the insect-elytra-inspired EBEP topologies achieve the highest Ec and the highest Vp simultaneously, demonstrating that the usual trade-off between stiffness and impact resistance can be overcome. A parametric study introduces the impactor-to-cell ratio (χ) metric which is defined as the impactor’s cross-sectional area divided by the square of the unit cell size. The perforation limit decreases exponentially for cell sizes above 2.5 mm (χ = 12.5) and stabilizes beyond 15 mm (χ = 1.4), implying that, beyond this point, larger unit cells do not contribute in augmenting the Vp as the improvement in impact stiffness diminishes.